EFFECTIVENESS OF PBL-BASED TORMA CODE INTERACTIVE MEDIA FOR ENHANCING ELEMENTARY STUDENTS’ CRITICAL THINKING AND PROBLEM-SOLVING SKILLS: A RESEARCH AND DEVELOPMENT STUDY - Qurrotul Ainiyyah; Joko Siswanto; Joko Sulianto (SOSIOEDUKASI, 2025)
This study aims to develop and evaluate the Torma Code interactive media based on Problem Based Learning (PBL) to enhance fourth-grade students’ critical thinking skills in learning IPAS on the topic of the visual sense. Employing the ADDIE development model—Analysis, Design, Development, Implementation, and Evaluation—the research involved expert validation, practicality testing with teachers and students, and effectiveness testing using pretest–posttest design. The results show that the media, teaching module, and test instruments achieved a “highly valid” classification with an average feasibility score above 90%, demonstrating strong content accuracy, linguistic clarity, and technical quality. The practicality test revealed positive responses from teachers (92.5%) and students (93.6%), indicating that the media are easy to use, engaging, and supportive of meaningful learning. The effectiveness test using paired sample t-test showed significant improvement in students’ critical thinking skills (Sig. < 0.05), with an N-Gain score of 0.55 categorized as moderate. These findings indicate that the Torma Code media effectively promotes contextual, collaborative, and student-centered learning. The product is therefore appropriate for broader implementation to support the Merdeka Belajar curriculum and strengthen scientific literacy in elementary schools.